Two Masquerades and their Spec(tac)ular Effects in Mary Robinson’s Walsingham - Sigler, David (Romanticism on the Net, 2007)
AbstractThis article examines Mary Robinson’s novel Walsingham (1797) from a Lacanian perspective. By offering readings of the novel’s two masquerade scenes from its narrator’s perspective within the imaginary order, and then tracing his confusion into the symbolic, this essay will seek to explain how (and why) Walsingham makes a spectacle of himself as he enters the very scene of social spectacle. We will find that Walsingham’s lingering in the imaginary—a product of his having made a series of specular identifications—establishes the conditions of his further humiliation even as it establishes the conditions for his eventual entry into the symbolic order. In attempting to forestall sexuation and even derive a certain enjoyment from its forestallment, Walsingham in effect reinforces the phallus and eventually bows to its demands. I argue that Walsingham dramatizes a transition between incommensurate modes of experience, that much of the novel’s plot stems from Walsingham’s entrapment in the imaginary, and that the novel is more invested in establishing characters within normative sexuated positions than enacting any sort of destabilizing gender trouble. Robinson’s novel reveals the force of the patriarchy (despite its unnaturalness) and suggests that sexual, gendered, and economic experience are interlaced through desire. The novel especially suggests that the subject is formed through the experience of the spectacle, and it deploys the entanglements of spectacle so that subjective experience can be seen to reorganize itself in the face of pressures political and social.